Lability of monofunctional cis-platinum adducts: role of DNA double helix. - Anin, M F (1992)
Recently, we have shown that the adduct formed in the reaction between the platinum-triamine complex cis-[Pt(NH3)2(N7-N-methyl-2-diazapyrenium)Cl]2+ and one single-stranded oligonucleotide was stable but became labile as soon as the platinated oligonucleotide was paired with its complementary strand (Gaucheron et al. Proc. Natl. Acad. Sci. USA 88, 3516-3519 (1991)). To generalize this finding we have now studied large DNA fragments containing several adducts. The stability of the adducts within single-stranded DNA is demonstrated by absorption spectrophotometry and by replication mapping experiments. Several approaches are used to prove the lability of the adducts within double-stranded DNA. Replication mapping experiments reveal that an unmodified single-stranded DNA when mixed with double-stranded DNA modified by the platinum-triamine complex behaves as a single-stranded DNA modified by the triamine complex. After double-stranded DNA is modified by the platinum-triamine complex, intrastrand and interstrand cross-links are progressively formed during subsequent incubation as revealed by transcription mapping experiments and gel electrophoresis under denaturing conditions. Finally, replication mapping experiments show that the lability of the adducts within a double-stranded DNA depends upon the nature of the flanking nucleotide residues. All these results support the proposal that the DNA double helix acts as a catalyst in the reaction between DNA, cis-diamminedichloroplatinum(II) and N-methyl-2,7-diazapyrenium.